Hi could some explain how about it is that the following can be proven true or false. $\displaystyle {\mathop{\rm Re}\nolimits} (z - w) = {\mathop{\rm Re}\nolimits} (z) - {\mathop{\rm Re}\nolimits} (w) $
Follow Math Help Forum on Facebook and Google+
Originally Posted by Craka Hi could some explain how about it is that the following can be proven true or false. $\displaystyle {\mathop{\rm Re}\nolimits} (z - w) = {\mathop{\rm Re}\nolimits} (z) - {\mathop{\rm Re}\nolimits} (w) $ Hint: Let $\displaystyle u+iv=w$ and $\displaystyle z=x+iy$.
View Tag Cloud